What does a book of late twentieth-century poetry look like: the peritext of 'Cumae' di Michele Sovente (Prassi Ecdotiche della Modernità Letteraria, 2019)
Moving from Gérard Genette’s reflections on paratexts and their role in the interpretation of a literary object, the paper aims to analyse a particular kind of paratext as the editorial peritext, considered as a fundamental part of the reception and reading of the poetry book. This study is dedicated to peritexts of Cumae, Michele Sovente’s fourth book, which is considered as a good case study to understand editorial strategies in the constitution and presentation of poetry books in the Italian late-Twentieth century.
Keywords: contemporary Italian poetry; Michele Sovente; peritext; paratext; poetry book